Photosensitizing properties of non-transition metal porphyrazines towards the generation of singlet oxygen - Seotsanyana-Mokhosi, Itumeleng (Rhodes University, Faculty of Science, Department of Chemistry, 2001)
Metallophthalocyanine complexes containing non-transition metals are very useful as sensitizers for photodynamic therapy, a cure for cancer that is based on visible light activation of tumour localized photo sensitizers. Excited sensitizers generate singlet oxygen as the main hyperactive species that destroy the tumour. Water soluble sensitizers are sought after for the convenience of delivery into the body. Thus, phthalocyanine (pc), tetrapyridinoporphyrazines (tppa) and tetramethyltetrapyridinoporphyrazines (tmtppa) with non-transition central metal atoms of Ge, Si, Sn and Zn were studied. First was the synthesis of these complexes, followed by their characterisation. The characterisation involved the use of ultraviolet and visible absorption spectroscopy, infrared spectroscopy, nuclear magnetic resonance spectroscopy, electrochemical properties and elemental analysis. Photochemical properties of the complexes were then investigated. Photolysis of these macrocycles showed two processes; -reduction of the dye and photobleaching, which leads to the disintegration of the conjugated chromophore structure of the dye. Photobleaching is the reductive quenching of the excited state of the sensitizers. The intensity of the quenching decreased progressively from tmtppa, tppa to pc metal complexes with photobleaching quantum yields, 6.6 x 10.5â »Â¹, 1.8 x 10.5â »Â¹ and 5.4 x 10â »â ¶ for Zntmtppa, Zntppa and Znpc, respectively. Efficiency of singlet oxygen sensitization is solvent dependent with very different values obtained for the same compound in different solvents, for example, 0.25 and 0.38 were observed as singlet oxygen quantum yields for Gepc complex in DMSO and DMF respectively. In DMSO the efficiency of Â¹Oâ‚‚ generation decrease considerably from pc to tppa and finally tmtppa. In water Getmtppa exhibits much higher singlet oxygen quantum yield, hence promising to be effective as a sensitizer for photodynamic therapy.
Keywords: Phthalocyanines; Photosensitization, Biological; Active oxygen -- Physiological effect; Photosensitizing compounds